Activation of GPR44 decreases severity of myeloid leukemia via specific targeting of leukemia initiating stem cells - Fenghua Qian; Shaneice K. Nettleford; Jiayan Zhou; Brooke E. Arner; Molly A. Hall; Arati Sharma; Charyguly Annageldiyev; Randy M. Rossi; Diwakar B. Tukaramrao; Deborpita Sarkar; Shailaja Hegde; Ujjawal H. Gandhi; et al. (Cell Reports, 2023)
Summary: Relapse of acute myeloid leukemia (AML) remains a significant concern due to persistent leukemia-initiating stem cells (LICs) that are typically not targeted by most existing therapies. Using a murine AML model, human AML cell lines, and patient samples, we show that AML LICs are sensitive to endogenous and exogenous cyclopentenone prostaglandin-J (CyPG), Δ12-PGJ2, and 15d-PGJ2, which are increased upon dietary selenium supplementation via the cyclooxygenase-hematopoietic PGD synthase pathway. CyPGs are endogenous ligands for peroxisome proliferator-activated receptor gamma and GPR44 (CRTH2; PTGDR2). Deletion of GPR44 in a mouse model of AML exacerbated the disease suggesting that GPR44 activation mediates selenium-mediated apoptosis of LICs. Transcriptomic analysis of GPR44−/− LICs indicated that GPR44 activation by CyPGs suppressed KRAS-mediated MAPK and PI3K/AKT/mTOR signaling pathways, to enhance apoptosis. Our studies show the role of GPR44, providing mechanistic underpinnings of the chemopreventive and chemotherapeutic properties of selenium and CyPGs in AML.